The impact of CFS/ME on employment and productivity in the UK: a cross-sectional study based on the CFS/ME national outcomes database - Sterne Jonathan AC; May Margaret T; Crawley Esther; Collin Simon M; Hollingworth William (BMC, 2011)
Abstract Background Few studies have investigated factors associated with discontinuation of employment in patients with CFS/ME or quantified its impact on productivity. Methods We used patient-level data from five NHS CFS/ME services during the period 01/04/2006-31/03/2010 collated in the UK CFS/ME National Outcomes Database. We used logistic regression to identify factors associated with discontinuation of employment. We estimated UK-wide productivity costs using patient-level data on duration of illness before assessment by a CFS/ME service, duration of unemployment, age, sex and numbers of patients, in conjunction with Office for National Statistics income and population data. Results Data were available for 2,170 patients, of whom 1,669 (76.9%) were women. Current employment status was recorded for 1,991 patients (91.8%), of whom 811 patients (40.7%) were currently employed and 998 (50.1%) had discontinued their employment "because of fatigue-related symptoms". Older age, male sex, disability, fatigue, pain, and duration of illness were associated with cessation of employment. In a multivariable model, age, male sex, and disability remained as independent predictors. Total productivity costs among the 2,170 patients due to discontinuation of employment in the years preceding assessment by a specialist CFS/ME service (median duration of illness = 36 months) were £49.2 million. Our sample was equivalent to 4,424 UK adults accessing specialist services each year, representing productivity costs to the UK economy of £102.2 million. Sensitivity analyses suggested a range between £75.5-£128.9 million. Conclusions CFS/ME incurs huge productivity costs amongst the small fraction of adults with CFS/ME who access specialist services.